Mircea Eliade’s cosmic Christianity: approaches to an interpretation - Sergey Tarasov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article deals with the construct of cosmic Christianity in Mircea Eliade's project of the history of religion. Links are established with other concepts of the author, such as creative hermeneutics, homo religiosus, the horror of history, etc. Parallels are also drawn with German Idealism, Protestantism, traditionalism, Jungian psychoanalysis, and conservative-revolutionary thought. The criticism of A. Lenel-Lavastin and D. Dubuisson is drawn upon, arguing that the construct of cosmic Christianity can work within a national-conservative synthesis, so that the nation becomes the guarantor of the purity of church tradition. Eliade's method by which he contrasts cosmic Christianity with Judeo-Christian messianism is discussed. As part of the concept of cosmic Christianity the implicit use of the author's original concept of tradition as a virtual chain of initiations is found. Eliade's assembly is viewed through the lens of P. Berger's social constructivism. It is argued that Berger bases his theory of secularization on Eliade's working definition of religion and concept of cosmization. The metaphysical opposition of Eliade's vital immanentism to Berger's transcendentalism is stated. Immanentism is correlated with the traditional and archetypal folk re-evaluation within cosmic Christianity, transcendentalism with the radical and historical interpretation of the Gospel in Lutheran theology. Eliade's history of religion is characterized as a modernist theory, with inherent qualities of M. such as: a desire for a totalizing worldview, an interest in building a synthetic ideology on the border of archaic myth and scientific knowledge, a sense of the removal of the divine and an acceleration of the end of history. A connection is established between Eliade's theory of religion and the metaphysical framework of the "natural" in Modern science and culture. The reality of the sacred is characterized as a living self-organizing system, and its manifestation as a hierophany of the natural. The conclusion is made that the essentialism and naturalism of such metaphysics do not allow the history of religion to transcend the categories of Modern science and culture, which, according to the author of the article, was the goal of Eliade's project.